Damping of post-impact vibrations - Muster, Michael; Amer, Hameed; Wood, David C.; Appleby-Thomas, Gareth J.; Wasmer, Kilian (Elsevier, 2019)
During the impact of a body on a plate, flexural waves are set which travel circularly outwards from the point of impact. These waves can be used to determine the properties of the impacting body. For accurate measurements, it is advantageous if both the flexural and compression waves pass the sensor just once without being backscattered or reflected from the boundaries. In this paper, various plate shapes are analysed to evaluate the shape which offers the best damping properties against an impact. Experimental analysis indicated that the reflection of the flexural waves can be halved using a plate with star-shaped 60° edges with a damping layer. The damping properties can be further doubled by using a star-shaped plate with power law edges in combination with a damping layer which is attached to the edges. The work reported here offers a possible solution to get significant damping properties. This is achieved by combining a damping layer with edge shaping against a strong single excitation event. The results demonstrate that it is a promising approach for an impact detection systems which could be equally applicable to acoustic damping applications.
Keywords: flexural vibrations; metallic plate; damping; boundary reflection